2001
DOI: 10.1034/j.1600-051x.2001.028002162.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered chemotactic behavior of crevicular PMNs in different forms of periodontitis

Abstract: These results indicate an increase of chemotactic activity from CF-PMN in patients with adult periodontitis, but on the other hand, a significant reduction of chemotactic responsiveness of these cells in LEOP and GEOP lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
26
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 39 publications
4
26
0
5
Order By: Relevance
“…Consistent with previous studies, 3–6 PMNs from our AgP cases exhibited significantly decreased chemotaxis toward fMLF and reduced FPR1 expression relative to PMNs from controls. We observed a 19% to 22% decrease in chemotaxis activity, whereas previous investigations reported a decrease of ∼20% to 50%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies, 3–6 PMNs from our AgP cases exhibited significantly decreased chemotaxis toward fMLF and reduced FPR1 expression relative to PMNs from controls. We observed a 19% to 22% decrease in chemotaxis activity, whereas previous investigations reported a decrease of ∼20% to 50%.…”
Section: Discussionsupporting
confidence: 92%
“…AgP is associated with invasive bacterial pathogens, such as Aggregatibacter actinomycetemcomitans (previously Actinobacillus actinomycetemcomitans ) and Porphyromonas gingivalis. 1,2 In addition, polymorphonuclear leukocytes (PMNs) from individuals affected by AgP exhibit reduced binding of N‐formylpeptides and a significant reduction in chemotactic activity toward formylpeptides relative to PMNs from healthy control subjects 3–6 …”
mentioning
confidence: 99%
“…Liu et al 40 showed that in two cases of Papillon-Lefevre syndrome, the chemotactic response of polymorphonuclear neutrophils (PMN) to FMLP and to IL-8 was depressed. Sigusch et al 41 observed that chemotactic behaviour of crevicular PMN is altered in localized early onset periodontitis (LEOP) and generalized early onset periodontitis (GEOP) lesions. In the present study, N-FMLP and casein were used as chemotactic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, synergistic or additive effects are to be expected, but probably also opposing, conflicting signals. Analyzing cells derived from the inflamed sites or from the peripheral blood of patients with systemic inflammatory diseases, including sepsis, gives some insight into the complex alterations of PMN (38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%